Síntese não aquosa de nanocristais de óxidos metálicos - Silva, Rafael Oliveira da (2008)
Nonaqueous synthesis routes to obtain metal oxide nanoparticles are a valuable alternative to the aqueous sol-gel processes, offering advantages such as high crystallinity at low temperatures and ability to control the crystal growth without the use of surfactants. In this work the synthesis of metal oxide species, such as SnO2, ZrO2, In2O3:Sn (ITO) and SnO2:Sb (ATO), is presented by a surfactant-free method, within some reaction system such as metal halides benzyl alcohol, metal alkoxides benzyl alcohol and metal acetylcetonates benzyl alcohol showing the versatility of this approach. The characterization of the products by XRD and HRTEM confirms the desired characteristics promised by the synthesis method.